Post-occupancy evaluation of Pagerjurang Permanent Housing after the Merapi volcanic eruption - Setiadi, Amos; Andriessen, Anouck; Anisa, Refranisa (Journal of Architecture and Urbanism, 2020)
Merapi Volcano erupted in 2010 and a community-based relocation of the destroyed area was implemented step by step in 2011, 2012, and 2013. This study, therefore, employed the Post-Occupancy Evaluation (POE) Method to investigate the ability of the new (permanent) housing model in Pagerjurang Kepuharjo Village, Yogyakarta to make its residents feel at home more than the old one and to determine the residents’ responses to their life after 10 years of living in the new model. Questionnaires were used to collect responses from 24 families and the results showed the residents became comfortable after 2 years of living in the new (permanent) housing due to the fulfillment of the post-disaster basic needs and do not wish to be back and live in their old houses. They were also reported to have felt satisfied with the new facilities such as the well-designed infrastructure including clean water, sanitation, electricity, streets, and evacuation routes as well as the well-designed layout with the houses built together (gotong-royong) to ensure more efficiency in terms of design. The model was also supported by the Government in terms of housing cost subsidy. In conclusion, the new community-based (permanent) housing has the ability to create a homey atmosphere and helps to ease the post-eruption recovery.